Lactate dehydrogenase and the severity of adenoviral pneumonia in children: A meta-analysis - Zou, Min; Zhai, Yang; Mei, Xiaoping; Wei, Xing (Frontiers in Pediatrics, 2023)
Background: Children with severe adenoviral pneumonia (ADVP) have poor prognosis and high risk of mortality. We performed a meta-analysis to evaluate the association between pretreatment lactate dehydrogenase (LDH) and severity, postinfectious bronchiolitis obliterans (PIBO), and mortality in children with ADVP. Methods: Relevant observational studies were identified by search of PubMed, Embase, Web of Science, Wanfang, and CNKI databases from inception to August 3, 2022. A random effect model was used to pool the results by incorporating the potential between-study heterogeneity. Results: Overall, 23 studies with 4481 children with ADVP were included in this meta-analysis. Results of meta-analysis showed that children with severe ADVP had a significantly higher level of pretreatment LDH as compared to those with non-severe ADVP (standard mean difference [SMD]: 0.51, 95% confidence interval [CI]: 0.36 to 0.66, p < 0.001; I2 = 69%). Besides, pooled results also suggested that the pretreatment LDH was significantly higher in children who developed PIBO as compared to those who did not (SMD: 0.47, 95% CI: 0.09 to 0.84, p = 0.02, I2 = 80%). Finally, results of the meta-analysis also confirmed that a higher pretreatment LDH (> 500 IU/L) was a risk factor of increased mortality during hospitalization (odds ratio: 3.10, 95% CI: 1.62 to 5.92, p < 0.001, I2 = 0%). Sensitivity analyses by excluding one dataset at a time showed consistent results. Conclusion: High pretreatment LDH may be associated with disease severity, development of PIBO, and increased risk of mortality in children with ADVP.